3-Nitroasterric Acid Derivatives from an Antarctic Sponge-Derived Pseudogymnoascus Sp. Fungus - Chavez-Rosales, R (American Chemical Society, 2015)
Four new nitroasterric acid derivatives, pseudogymnoascins A-C (1-3) and 3-nitroasterric acid (4), along with the two known compounds questin and pyriculamide, were obtained from the cultures of a Pseudogymnoascus sp. fungus isolated from an Antarctic marine sponge belonging to the genus Hymeniacidon. The structures of the new compounds were determined by extensive NMR and MS analyses. These compounds are the first nitro derivatives of the known fungal metabolite asterric acid. Several asterric acid derivatives isolated from other fungal strains have shown antibacterial and antifungal activities. However, the new compounds described in this work were inactive against a panel of bacteria and fungi (MIC > 64 μg/mL). © 2015 The American Chemical Society and American Society of Pharmacognosy.